Role of Genetic Ancestry in 1,002 Brazilian Colorectal Cancer Patients From Barretos Cancer Hospital - Durães, Ronilson Oliveira; Berardinelli, Gustavo Noriz; da Costa, Allini Mafra; Scapulatempo-Neto, Cristovam; Pereira, Rui; Oliveira, Marco Antônio; Guimarães, Denise Peixoto; Reis, Rui Manuel (Frontiers in Oncology, 2020)
Background: Colorectal cancer (CRC) is the third most frequent and the second deadliest cancer worldwide. The ethnic structure of the population has been gaining prominence as a cancer player. The purpose of this study was to determine the genetic ancestry of Brazilian CRC patients. Moreover, we intended to interrogate its impact on patients' clinicopathological features. Methods: Retrospective observational cohort study with 1,002 patients with CRC admitted from 2000 - 2014 at Barretos Cancer Hospital. Following tumor DNA isolation, genetic ancestry was assessed using a specific panel of 46 ancestry-informative markers. Survival rates were obtained by the Kaplan-Meier method, and the log-rank test was used to compare the survival curves. Multivariable Cox proportional regression models were used to estimate hazard ratios (HR). Results: We observed considerable admixture in the genetic composition, with the following average proportions: European 74.2%, African 12.7%, Asian 6.5%, and Amerindian 6.6%. The multivariate analysis for specific-cancer survival showed that clinical stage, lymphovascular invasion, and the presence of recurrence were associated with an increased relative risk of death from cancer (p<0.05). High African proportion was associated with younger age at diagnosis, while high Amerindian proportion was associated with mucinous histological subtype. Conclusions: This represents the larger assessment of genetic ancestry in a population of Brazilian patients with CRC. Brazilian CRC patients exhibited similar clinicopathological features, as described in Western countries. Impact: Genetic ancestry components corroborated the significant admixture, and importantly, patients with high African proportion develop cancer at a younger age.